EFFECTIVENESS OF SLOW STROKE BACK MASSAGE ON FATIGUE OF HEMODIALYSIS PATIENTS AT RSAU DR. M. SALAMUN BANDUNG IN 2024 - Syahwaludin DA; Ramadhan A; Muhtadin M; Pitono A.J; Tohri T (UNIVERSITAS SARI MUTIARA INDONESIA, 2025)
Background: Chronic Kidney Disease (CKD) involves the gradual deterioration of renal function, resulting in the accumulation of metabolic waste and excess fluids, known as uremia. Hemodialysis serves as a renal replacement therapy that cleanses the blood by passing through an artificial kidney (dialyzer), eliminating toxins and surplus fluid through the processes of diffusion and ultrafiltration. Persistent tiredness among patients undergoing hemodialysis typically stems from treatment-related complications such as minor blood loss, resulting anemia, and ongoing uremic toxin retention. Research Objectives: To determine the effectiveness of SSBM on fatigue of HD patients. Research Method: : this research is quantitative research. Using pre-experimental pre-test post-test research with one group design. The sampling technique obtained by total sampling with a total of 40 male respondents. Using the Wilcoxon test to determine differences before and after intervention.. Result: The results of this study using the Wilcoxon test showed a p-value <0.001. Conclusion: There is a difference in fatigue scores before and after SSBM intervention